Emergence of Novel RNA-Editing Sites by Changes in the Binding Affinity of a Conserved PPR Protein. (13th October 2022) - Loiacono, F Vanessa; Walther, Dirk; Seeger, Stefanie; Thiele, Wolfram; Gerlach, Ines; Karcher, Daniel; Schöttler, Mark Aurel; Zoschke, Reimo; Bock, Ralph
Abstract: RNA editing converts cytidines to uridines in plant organellar transcripts. Editing typically restores codons for conserved amino acids. During evolution, specific C-to-U editing sites can be lost from some plant lineages by genomic C-to-T mutations. By contrast, the emergence of novel editing sites is less well documented. Editing sites are recognized by pentatricopeptide repeat (PPR) proteins with high specificity. RNA recognition by PPR proteins is partially predictable, but prediction is often inadequate for PPRs involved in RNA editing. Here we have characterized evolution and recognition of a recently gained editing site. We demonstrate that changes in the RNA recognition motifs that are not explainable with the current PPR code allow an ancient PPR protein, QED1, to uniquely target the ndhB -291 site in Brassicaceae. When expressed in tobacco, the Arabidopsis QED1 edits 33 high-confident off-target sites in chloroplasts and mitochondria causing a spectrum of mutant phenotypes. By manipulating the relative expression levels of QED1 and ndhB -291, we show that the target specificity of the PPR protein depends on the RNA:protein ratio. Finally, our data suggest that the low expression levels of PPR proteins are necessary to ensure the specificity of editing site selection and prevent deleterious off-target editing.